(untitled) (International Journal of Engineering and Computer Science, 2014)
This Paper describes the theory and simulation by mat lab of flexible Alternative Current Transmission Systems (FACTS) devices used in the disturbed power systems. One of these devices, Unified Power Flow Controller (UPFC) will be chosen for a specific application, detailed in this Project. Simulation investigate the effect of UPFC on the voltage of the related bus, it also considers the effect on the amount of active and reactive power flowing through the transmission system. Finally simulation results have been presented to indicate the improvement in the performance of the UPFC to control voltage in disturbed power systems.